The Gal3p-Gal80p-Gal4p Transcription Switch of Yeast: Gal3p Destabilizes the Gal80p-Gal4p Complex in Response to Galactose and ATP - Sil, Alok Kumar (American Society for Microbiology, 1999)
The Gal3, Gal80, and Gal4 proteins of Saccharomyces cerevisiae comprise a signal transducer that governs the galactose-inducible Gal4p-mediated transcription activation of GAL regulon genes. In the absence of galactose, Gal80p binds to Gal4p and prohibits Gal4p from activating transcription, whereas in the presence of galactose, Gal3p binds to Gal80p and relieves its inhibition of Gal4p. We have found that immunoprecipitation of full-length Gal4p from yeast extracts coprecipitates less Gal80p in the presence than in the absence of Gal3p, galactose, and ATP. We have also found that retention of Gal80p by GSTG4AD (amino acids [aa] 768 to 881) is markedly reduced in the presence compared to the absence of Gal3p, galactose, and ATP. Consistent with these in vitro results, an in vivo two-hybrid genetic interaction between Gal80p and Gal4p (aa 768 to 881) was shown to be weaker in the presence than in the absence of Gal3p and galactose. These compiled results indicate that the binding of Gal3p to Gal80p results in destabilization of a Gal80p-Gal4p complex. The destabilization was markedly higher for complexes consisting of G4AD (aa 768 to 881) than for full-length Gal4p, suggesting that Gal80p relocated to a second site on full-length Gal4p. Congruent with the idea of a second site, we discovered a two-hybrid genetic interaction involving Gal80p and the region of Gal4p encompassing aa 225 to 797, a region of Gal4p linearly remote from the previously recognized Gal80p binding peptide within Gal4p aa 768 to 881.